2017
DOI: 10.3897/zookeys.705.11852
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genomes from two species of Chinese freshwater crabs of the genus Sinopotamon recovered using next-generation sequencing reveal a novel gene order (Brachyura, Potamidae)

Abstract: Recent morphological and molecular evidence has challenged classical interpretations of eubrachyuran phylogeny and evolution. Complete mitochondrial genomes of two species of potamid freshwater crabs, Sinopotamon yaanense and Sinopotamon yangtsekiense were obtained using next-generation sequencing. The results revealed a novel gene order with translocations of a five-gene block and a tRNA gene in comparison to available brachyuran mitochondrial genomes. DNA sequence comparisons position the Potamidae, a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 90 publications
1
13
0
Order By: Relevance
“…The monophyly of Potamidae and Parathelphusidae was confirmed based on morphological and molecular analyses. However, there still were uncertainties regarding the phylogenetic placement of Potamidae and Parathelphusidae ( Xing et al, 2017 ). Von Sternberg and Cumberlidge (2001) suggested that these two families Potamidae and Parathelphusidae should be placed in Thoracotremata.…”
Section: Resultsmentioning
confidence: 99%
“…The monophyly of Potamidae and Parathelphusidae was confirmed based on morphological and molecular analyses. However, there still were uncertainties regarding the phylogenetic placement of Potamidae and Parathelphusidae ( Xing et al, 2017 ). Von Sternberg and Cumberlidge (2001) suggested that these two families Potamidae and Parathelphusidae should be placed in Thoracotremata.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial genome assemblies were conducted in Geneious 11.1.2 using parameter settings described previously [22, 25]. Protein-coding genes (PCGs) were identified by finding the ORFs (https://www.ncbi.nlm.nih.gov/orffinder) using the invertebrate mitochondrial genetic code.…”
Section: Methodsmentioning
confidence: 99%
“…Mitogenomic data, including both primary sequences and gene rearrangements, have been shown to contain useful phylogenetic information for inferring the evolutionary relationships among eubrachyurans [1722]. Compared to the data on the partial fragments of genes, phylogenetic reconstruction using mitogenomic data could help avoid the interference of nuclear pseudogenes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Those in favour of monophyletic Heterotremata argue on the basis of molecular data (Tsang et al, 2014) but also morphological data such as endosternite characters (sella turcica, Secretan, 1998) and the position of gonopores (Guinot, 1977). Then again molecular data by Bracken et al (2009), Shen et al (2013), Yuhui et al (2017) and Basso et al (2017) as well as morphological data such as spermatozoal ultrastructure (Jamieson et al, 1995;Jamieson & Tudge, 2000) and foregut ossicles (Brösing et al, 2006) (Shen et al, 2013;Basso et al, 2017;Yuhui et al, 2017). Additionally, some eubrachyuran groups might not be monophyletic (Schubart & Reuschel, 2009;Lai et al, 2011Lai et al, , 2014.…”
Section: 12| What We (Do Not) Know About the Phylogeny Of Eubrachyuramentioning
confidence: 96%
“…Ahyong et al (2007) resolved hymenosomatids as close relatives of Dorippoidea within heterotremes, whereas the analysis of Teske et al (2009) resulted in a close relationship to Potamidae. Interestingly enough, the latter have been recently discussed as closely related or even as sister group to Thoracotremata (Shen et al, 2013;Basso et al, 2017;Tang et al, 2017;Yuhui et al, 2017). Guinot (2011), Guinot et al (2013), and Davie et al (2015b) discussed the contradicting data concerning the hymenosomatid position within the Eubrachyura.…”
Section: Hymenosomatidaementioning
confidence: 99%